Timing of river capture in major Yangtze River tributaries: Insights from sediment provenance and morphometric indices - Fan, Niannian; Kong, Ping; Robl, Jörg Christian; Zhou, Hongwei; Wang, Xianyan; Jin, Zhangdong; Liu, Xingnian (Geomorphology (Amsterdam, Netherlands), 2021)
The eastern margin of the Tibetan Plateau represents one of the morphologically most active regions on Earth, where the interplay of recent crustal deformation and subsequent fluvial landscape adjustment has affected the course of continental-scale rivers by river piracy events. Based solely on field observations, such an event has been hypothesised for two of the largest tributaries of the Yangtze River: the Jialing and Hanjiang Rivers. To test this hypothesis, we employ a novel combination of independent methods including a provenance study based on age distributions of detrital zircons from both modern riverbeds and river terraces and a morphometric analysis of river channels and drainage divides. We supported the morphometric analysis with a time-dependent numerical model describing the evolution of river channel long profiles and drainage divides in a succession of river capture events. Analysed zircon ages show clearly distinguishable distributions for the modern Jialing and Hanjiang Rivers, but similar distributions for the recent Hanjiang River up to its topmost terraces. This suggests that the capture of the Hanjiang headwaters by the Jialing River is unlikely to have taken place during the last 1.2 million years. However, several knickpoints in the main stem and the tributaries of the Jialing River cluster at an elevation of about 900 m and separate steeper (downstream) from less steep channel segments (upstream), which is consistent with the morphological expression of a major capture event. χ mapping indicates drainage divide asymmetry at catchment scale with on average steeper rivers on the Jialing side, whereas Gilbert metrics show a symmetric divide at hillslope scale. This numerical model explains this apparent contradiction by the travel time of capture-related knickpoints from the capture point towards the watershed, where χ mapping indicates divide asymmetry immediately after the river capture, while Gilbert metrics are only affected as soon as the knickpoints reach the channel heads and the divide effectively starts moving. Based on knickpoint travel distances and constraints on regional incision / uplift rates, we estimate the possible date of river capture to be the Pliocene. This is earlier than the formation of the terraces investigated in the provenance study but recent enough that most of the drainage divides are still unaffected and currently almost stable. Only the wind gap located in the almost dry valley connecting the two competing drainage systems is likely to have shifted towards the Hanjiang side. We suggest that this resulted in the capture of another important tributary of the Hanjiang River (the Heishui River) by the Jialing drainage system. Our results illustrate the complex evolution of drainage networks along the eastern margin of the Tibetan Plateau, and highlight the importance for combining provenance and morphometric analyses in regions of active landscape rejuvenation where river captures are likely to occur. •Study of river capture between Yangtze River tributaries, Eastern Tibetan Plateau•Applies provenance, fluvial metrics and modelling to Jialing and Hanjiang Rivers•Modern and river terrace zircon ages suggest that capture is older than 1.2 Ma.•River profile and drainage divide metrics record morphological response of capture.•Modelling suggests a Pliocene capture as a regional response to plateau uplift.